2016
DOI: 10.1002/pro.2834
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of native and non-native ubiquitin oligomers reveals analogous structures and reactivities

Abstract: Ubiquitin (Ub) chains regulate a wide range of biological processes, and Ub chain connectivity is a critical determinant of the many regulatory roles that this post-translational modification plays in cells. To understand how distinct Ub chains orchestrate different biochemical events, we and other investigators have developed enzymatic and non-enzymatic methods to synthesize Ub chains of well-defined length and connectivity. A number of chemical approaches have been used to generate Ub oligomers connected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 78 publications
3
22
0
Order By: Relevance
“…c , Kinetic parameters for all independently performed experiments of Lys11, Lys63 and Lys48 diUb cleavage by Cez WT. Values are in good agreement with previously published parameters derived from gel-based studies41. d , Summary of kinetic parameters for Lys11-, Lys63- and Lys48-linked diUb cleavage by Cez E157K.…”
Section: Extended Datasupporting
confidence: 88%
“…c , Kinetic parameters for all independently performed experiments of Lys11, Lys63 and Lys48 diUb cleavage by Cez WT. Values are in good agreement with previously published parameters derived from gel-based studies41. d , Summary of kinetic parameters for Lys11-, Lys63- and Lys48-linked diUb cleavage by Cez E157K.…”
Section: Extended Datasupporting
confidence: 88%
“…Recent biophysical analysis of thiol-ene produced Ub chains compared with native conjugates was carried out in order to ascertain the extent to which thiol-ene-generated Ub conjugates successfully mimic the native isopeptide bond. For the most part, high similarity between native and the non-native surrogates was found (by SAXS analysis) but DUB activity assays indicated that for OTUB1, the non-native surrogate was an unsuitable mimic of the native linkage [ 143 ].…”
Section: Non-native Ubiquitinationmentioning
confidence: 99%
“…The final product 6 carrying a Lys27 mimic link (Lym27 diUb) was obtained on a 50 mg scale in a total yield of 6 % after folding (Figure B–D). To verify that the sulfur atom replacement did not affect the interaction, the binding affinity between Lym27 diUb and UCHL3 was determined ( K D =160±40 n m ; Figure E) and it is similar to that of wild‐type K27 diUb ( K D =190±30 n m ). Moreover, Lym27 diUb could be cleaved by a K27‐selective deubiquitinase, OTUD2, to a similar level as the wild‐type (Supporting Information, Figure S7).…”
Section: Figurementioning
confidence: 60%